Dampak Ekonomi Penerapan Community Based Tourism Di Desa Wisata Wayang, Kepuhsari, Kecamatan Manyaran Kabupaten Wonogiri - Anandito, Erlangga Singgih; Setiawan, Bakti (Jurnal Ilmiah Pariwisata, 2018)
Kepuhsari Village is a puppet craft village, located in Wonogiri Regency. Existing cultural resources are able to be optimized as a tourist attraction with the characteristic of making wayang kulit, through a complete process, namely cutting and playing. The emergence of the Wayang Village Tourism Village is a tangible form of the application of the Community Based Tourism concept. This research was proposed to find out: the economic impact of the implementation of community-based tourism in the Wayang Village Tourism Village. This study uses a qualitative approach, by collecting primary data through interviews and observations to explore more deeply the phenomena that occur, supported by regional mapping and documentation. The primary data collection will be reduced to draw a red thread from the statements that appear, supported by secondary data that is deemed appropriate to the context of the problem. Analysis using qualitative descriptive analysis. This research produces findings, namely: Economic benefits, changes in puppet production patterns, and the use of cultural resources are strongly influenced by tourism, although the perceived direct economic impact is relatively low but tourism presence is able to move the economic wheel of the Kepuhsari village community.